Dr Kazuo Inamori's management praxis and philosophy : a response to the profit-maximisation paradigm /: a response to the profit-maximisation paradigm. (2022) - Kase, Kimio, 1949-; Choi, Eugene; Nonaka, Ikujirō, 1935-
No abstract available